Olfactory epithelium organization of the grass carp (Ctenopharyngodon idella) at the ultrastructural level: SEM and TEM observations - Elsheikh, Eman H.; Hassan, Sahar S.; Al-Zahaby, Sheren A. (Journal of Advanced Veterinary Research, 2024)
Olfaction is the major sense of smell in teleost involved in many physiological response and habitat acclimatization including food searching, migration for spawning, predator avoidance, reproduction behavior, as well as identification of fish of the same species. Our study illustrates the ultrastructure of the olfactory rosette of the grass carp Ctenopharyngodon idella (Cuvier and Valenciennes, 1844) by using Scanning Electron Microscope (SEM) and transmission Electron Microscope (TEM). Herein, the peripheral olfactory organs are represented by two olfactory rosettes lying in two nasal chambers, one on each side of fish snout. Each nasal chambers opens to the exterior by two nostrils a narrow inlet and wider outlet, segregated by a somewhat elevated, nasal bridge. The two nostrils are somewhat faraway as far as length of rosetteâ€™s length to permit entering and leave water flow bearing odorant molecules to the nasal cavities. The SEM revealed that each olfactory rosette is elongated oval-shaped and made up of 48-50 foliar lamellae transversely arranged on both sides of a narrow median raphe. Alongside, the magnitude of lamellae differs in relation to their location on the raphe, since the larger are in the middle whereas their dimensions gradually reduced towards both ends of the rosette indicating that the number and magnitude of lamellae increase as the fish grow. Moreover, the lamellar surface comprises sensory and non-sensory areas concealed in a mucous layer and not distributed uniformly within the epithelial surface of the olfactory lamellae. Accordingly, The TEM observations indicated that the sensory areas holds four main receptor neurons, two Â are major including ciliated and microvillous receptor cells bearing either cilia or microvilli, respectively emitted from a dendritic knob. Additionally, two other minor rod-tipped and crypt cells bearing a compound rod cilium, or few microvilli and occult cilia emitted also from dendritic knob were rarely observed. From the other side, the non-sensory area comprises cylindrical flat top surface; ciliated non-sensory cells with motile long kinocilium and nonciliated stratified epithelial cells with fingerprint-like microridges both are mainly of supporting in addition of and ovoid goblet mucous cells in-between and stem basal cells. Collectively, our study revealed the general organization and ultrastructure of an important economic teleost fish that affects feeding habitat and has an important influence on the fish food intake.